Analysis of the Main International Tourist Arrivals to Thailand and Their Impacts on Thailand’s Tourism Industry - Chayakul, Chariya (KASEM BUNDIT JOURNAL, 2017)
Thailand’s tourism industry grew rapidly in the past decade. The source of Thailand’s tourism growth came from three main regions: East Asia, Southeast Asia and Europe. This paper focuses on analyzing the three main regions of international tourist arrivals to Thailand and their impacts on Thailand’s tourism industry